Orbital Fractures: Pathophysiology and Implant Materials for Orbital Reconstruction - Strong, E. Bradley (Facial Plastic Surgery, 2014)
Among midfacial fractures, the frequency of orbital injuries is surpassed only by nasal fractures. A clear understanding of orbital anatomy and the pathophysiology of these injuries is critical to accurate diagnosis, precise surgical reconstruction, and successful clinical outcomes. This chapter reviews the mechanism of injury and pathophysiology of orbital fractures as well as the implant materials that are currently used for surgical reconstruction.
Keywords: orbital anatomy; orbital fracture; orbital reconstruction; orbital implant